Mapping the Evolution of Digital Marketing Strategies in Thailand A Systematic Literature Review of Emerging Trends - Fateemah Yanya (Jurnal Manajemen dan Bisnis Indonesia, 2026)
The rapid expansion of Thailand’s digital economy has transformed how organizations design and implement marketing strategies, yet academic understanding of this evolution remains fragmented and often focuses on isolated digital marketing dimensions. This study aims to map the evolution of digital marketing strategies in Thailand by synthesizing emerging trends and developing an integrated conceptual perspective within the context of an emerging digital economy. Using a Systematic Literature Review (SLR) approach based on the PRISMA framework, this study analyzed 29 peer-reviewed articles published between 2015 and 2026 retrieved from Scopus, ScienceDirect, Google Scholar, SpringerLink, and Emerald Insight. The selected studies were examined through thematic synthesis to identify patterns of strategic transformation, technological shifts, and research gaps. The findings reveal a significant transition from social media–based visibility strategies toward integrated ecosystems driven by artificial intelligence, data analytics, influencer economy, and social commerce. Contemporary digital marketing practices in Thailand are increasingly characterized by personalization, platform-based interaction, and analytics-driven decision-making, reflecting a shift from tactical promotion toward adaptive strategic infrastructure. The study also identifies critical gaps related to ethical governance, organizational culture, and digital ecosystem integration. Conceptually, this research contributes by proposing an integrated framework that connects AI marketing, influencer economy, social commerce, and data-driven marketing within the broader evolution of digital marketing strategies in emerging economies. Overall, the evolution of digital marketing in Thailand demonstrates a multidimensional transformation shaped by technological innovation, participatory digital culture, and changing consumer behavior.